Comparison of static and dynamic analyses on exchange rate regimes in East Asia - Naoyuki Yoshino; Sahoko Kaji; Tamon Asonuma (Asian Development Bank Institute (ADBI), 2015)
This paper compares three methods of analyzing exchange rate regimes in East Asia: static analysis, conventional dynamic analysis, and dynamic transition analysis. First we provide quantitative results that both estimated parameters for Thailand and time intervals are applied symmetrically across the three approaches. Our comparable simulation results illustrate how these three analyses are mutually related. Comparisons across the three methods demonstrate limitations of the static and conventional dynamic analyses where exchange rate regimes remain unchanged over the analysis horizon. Moreover, we emphasize three advantages of the dynamic transition analysis over the static and conventional dynamic analyses in that shifts from the current regime to alternative regimes are contrasted with a benchmark case of maintaining the current regime over the analysis horizon.
Keywords: F33; F41; F42; 330; exchange rate regimes; dynamic transition analysis; capital account management; exchange rate stability